24 Wikipedia medical page editing as a platform to teach evidence-based medicine. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Murray, Heather; Walker, Melanie; Maggio, Lauren; Dawson, Jennifer
Abstract : Objectives: Medical articles on Wikipedia are viewed over 10 million times a day and Wikipedia is arguably the most-read medical information platform on the internet. The quality and evidence-base of Wikipedia medical articles are improving but there is an ongoing need for refinement and updating. Editing and improving these articles represents a 'whole task' application of the steps in Evidence-Based Medicine (EBM) while simultaneously contributing to an altruistic mission of knowledge sharing and health advocacy. Involving medical students in Wikipedia-editing initiatives provides an opportunity for application of EBM skills while also improving medical articles on Wikipedia. We developed an embedded longitudinal Wikipedia editing project as part of a first year critical appraisal course in the School of Medicine at Queen's University, Canada. Our goal was to evaluate the design and implementation of this project using student feedback in a structured survey. Method: Students completed online training modules provided by Wikipedia and chose a medical article to improve. Students worked in small groups to assess their articles, made suggestions for improvement, and searched the literature for high-quality secondary sources containing suitable evidence. They posted suggested changes to the Wikipedia community for feedback and consulted with a faculty expert prior to making final page edits. All students completed a Wikipedia project evaluation form. Feedback was sought on the perceived strengths, weaknesses, struggles in project completion, and suggestions for improvement going forward. Using the Five-Dimensional Framework for Authentic Assessment (Gulikers, JTM et al., 2004), student feedback data was reviewed by two investigators (MW and LM) who independently identified barriers to/facilitators in project completion and assigned them into one of five dimensions relating to (1) the task (2) the physical/virtual context (3) the social context; (4) the result and (5) the criteria for evaluation. Results: One hundred and one students made over 1000 edits to 16 articles, adding over 10 000 words to the pages, all with appropriate secondary source citations. Based on a preliminary review of the feedback data, students enjoyed applying the critical appraisal skills taught within the broader scope of the course (task), they liked making an improvement to a highly accessed public resource (result), they reported positive collaboration within their teams (social context), and they enjoyed learning about the process involved in forming and editing a Wikipedia medical page (task). Barriers to the project identified by the students included a lack of clarity regarding assignment expectations (task), frustration with Wikipedia coding (task), difficulty engaging with the Wikipedia editors/community (social context), distrust of Wikipedia editors as content experts (social context), and a perceived mismatch in efforts dedicated to the assignment and the resulting change/impact on their Wikipedia medical page (result). Conclusions: Initial results highlight important barriers and facilitators identified by medical students in engaging with and completing the longitudinal Wikipedia assignment as part of their first-year critical appraisal, research and life long learning course. These results will inform the future delivery and assessment of this assignment in an effort to increase engagement among first-year medical students in improving one of the leading sources of online health information worldwide.